Asuhan Keperawatan Dengan Gangguan Sistem Pencernaan: Demam Thypoid Pada Anak dengan Terapi Kompres Bawang Merah di Rumah Sakit Bhayangkara Mohamad Hasan Palembang - Fitri Afdhal; Erik Rosadi; Ria Wulandari; Ine Nadilla Vinka Putri (JURNAL KESEHATAN TERAPAN, 2026)
Bacterial infection caused by Salmonella typhi affecting the digestive system results in typhoid fever, which can lead to inflammation and increased body temperature. Consumption of food or beverages contaminated with Salmonella typhi may cause typhoid fever. In addition, transmission can occur through direct contact with the feces, urine, or secretions of individuals infected with typhoid fever. Objective: To implement nursing care for a pediatric patient with a digestive system disorder: typhoid fever, by applying shallot compress therapy at Bhayangkara Mohamad Hasan Hospital, Palembang, in 2025. The study employed a case study design. Data were collected through interviews with the patient’s family, observation, physical examination, and documentation. Shallot compress therapy was administered once daily in the morning for three consecutive days. After assessment, a reduction in body temperature was observed following the application of shallot compress therapy. On the first day, the patient’s temperature was 39.2°C; after a 15-minute morning compress session, the temperature decreased to 38.5°C. On the second day, the temperature decreased to 37.5°C, and on the third day, it further decreased to 36.5°C. Conclusion: Shallot compress therapy is expected to serve as an alternative non-pharmacological intervention for managing hyperthermia in nursing care. This study is expected to provide knowledge regarding the implementation of non-pharmacological management to help reduce fever in children.